The Sijujju Sulo Tradition as a Media of Community Communication in Pongka Village, Tellu Siattinge District, Bone Regency - Arniati Arniati; Kurniati Abidin (Palakka : Media and Islamic Communication, 2022)
The Sijujju Sulo tradition is a tradition that is still maintained by the people of Pongka Village, Tellu Siattinge District, Bone Regency, which is held every three years to commemorate the birth of Pongka Village. This tradition is carried out continuously and routinely until now. The process of implementing the Sijujju Sulo tradition presents cultural rituals with various symbols full of good meaning, togetherness, local friendliness, kinship, simplicity, the spirit of mutual cooperation and hard work in opposing evil, and always being grateful to the Creator and Ruler of the universe. Allah SWT. by His grace and mercy. The Sijujju Sulo tradition is one of the communication media for the people of Pogka Village to convey messages or advice from their predecessors, especially those who are considered to be the originators and  founders of Pongka Village. Each implementation process and the equipment used has a symbol, namely a form of non-verbal communication that is full of messages and meanings.